Open surgery and minimally invasive repair of acute Achilles tendon rupture: stratified outcomes based on immobilization duration in a prospective cohort study - Yuan Cao; Xiuzhi Li; Zengzhen Cui; Yang Lv; Gao Si (Journal of Orthopaedic Surgery and Research)
Abstract Background Acute Achilles tendon rupture (AATR) surgical repair debates center on the clinical efficacy of minimally invasive surgery (MIS) versus open surgery (OS), with immobilization duration poorly stratified. This prospective cohort study aimed to compare clinical outcomes of OS and MIS for AATR repair and evaluate the impact of immobilization duration (0, 2, or 4 weeks) on postoperative rehabilitation. Methods A total of 474 patients undergoing surgical repair for acute AATR were stratified into six groups based on surgical approach (OS: 265 cases; MIS: 209 cases) and immobilization duration (0, 2, or 4 weeks). The primary outcomes were postoperative complications, while secondary outcomes included recovery times for Achilles tendon function. Data regarding the operative times, incision lengths, the visual analog scale (VAS) score, the Achilles tendon Total Rupture Score (ATRS), and the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Scale score, and the relative Achilles tendon resting angle (ATRA) were also collected. Results MIS groups demonstrated significantly shorter operative times (34.1–34.4 vs. 45.1–46.1 min, P < 0.001) and reduced incision lengths (2.2–2.4 vs. 4.5–4.7 cm, P < 0.001) compared to OS. Postoperative VAS scores were markedly lower in MIS cohorts during the first 2 weeks (P < 0.001), with pain resolution comparable across all groups by 8 weeks. Despite the superior early functional recovery in PF (9.1–33.4 vs. 14.6–38.9 days, P < 0.001), Group D and E exhibited higher re-injury rates compared to OS (P < 0.05), in which Group D also demonstrated higher re-operation rates (5.6% vs. 0, P = 0.038). Prolonged immobilization (4 weeks) delayed functional recovery in both cohorts (P < 0.001). While transient differences in AOFAS Ankle-Hindfoot Scale and ATRS scores were observed at intermediate time points, all groups achieved near-maximal functional scores by 48 weeks, with no significant between-group differences (P > 0.05). Relative ATRA exhibited no significant intergroup differences at 48 weeks postoperatively (P > 0.05). Conclusion MIS for acute Achilles tendon rupture achieves faster early recovery but carries higher re-injury risks, mitigated by 4-week immobilization. OS benefits from shorter (2-week) immobilization. Both approaches yield equivalent long-term functions, emphasizing the need for tailored protocols and refined MIS techniques to optimize outcomes. Trial registration NCT04663542.